Ghrelin ameliorates chronic obstructive pulmonary disease–associated infllammation and autophagy. (19th May 2020) - Song, Beibei; Yan, Xixin; Li, Rongqin; Zhang, Huiran
Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic and devastating condition characterized by poor airflow and breath. Smoking and other environmental factors–caused inflammations triggered excessive autophagy of normal lung epithelial cells, eventually leading to impaired lung functions. Previous studies showed that ghrelin exhibited beneficial effects on patients with COPD. However, the mechanisms underlying this impact remained largely unknown. In this study, in vitro and in vivo models of COPD‐associated inflammation were established, and we found that inflammation and autophagy were abonormally activated through nuclear factor kappa b (NF‐κB) and activator protein‐1 (AP‐1) signaling pathways. Interestingly, ghrelin could inhibit the excessive inflammation pathways and autophagy induced by particle matter and/or cigarette extract in bronchial epithelial cells. Furthermore, NF‐κB and AP‐1 signaling were both inhibited while lung functions were significantly improved. Taken together, identification of downstream signaling of ghrelin in inflammation provided a new avenue in the treatment of COPD.